Rare metals in minerals of stanniferous metasomatites from the Verkhneurmiysky ore cluster (Far East, Russia) - Alekseev Viktor I. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Санкт-Петербургский горный университет», 2018)
This article is dedicated to the rare metal mineralization of stanniferous metasomatites of the Verkhneurmiysky ore cluster in the Far East of Russia. The mineral composition of metasomatites, formed during the five stages of the zwitter-tourmalineite stanniferous complex formation was studied. These stages were characterized as biotite-sericite, muscovite-quartz, siderophyllite-topaz, quartz-tourmaline, and chlorite-sericite. Rare metal-bearing minerals were selected and the concentrations of rare metals were estimated. The ore and geochemical types of the studied metasomatites were determined. There was shown the presence of many rare metal-bearing minerals in the composition of stanniferous metasomatites in this region. The set of the rare metals (Nb, Ta, W, Y, REE (from La to Lu), Be, Li, Zr, Hf, In, Sc, Se, and Cd) is of strategic importance for the development of the Russia mineral resources base. Minerals concentrating rare metals were divided into two types: minerals, containing rare metals due to its stoichiometry and minerals (if vein and ore origin) with isomorphic impurities of rare metals. There was traced the sequence of rare metal-bearing minerals formation and the evolution of their composition. Minerals of rare metals were formed throughout the history of the zwitter-tourmalineite formation, starting from the pre-ore stage of biotite feldspatholites to the post-ore of chloritites stage, including the zwitter ore stage. It was also shown a stepwise decrease in the intensity rare metal-bearing minerals formation and the evolution of the mineralization composition from lithophilic rare metals to chalcophylic ones: (LREE, Zr, Hf) → (W, Nb, Ta, Y, HREE, Sc) → (Sn, In, Cd, Se). Magmatic, metasomatic and crystal chemical factors affecting the rare metal-bearing minerals formation in the Verkhneurmiysky ore cluster have been revealed. The ore cluster's prospects are related to the presence of lithiumfluoric granites of the Pravourmiyskiy complex, controlling the tungsten-stanniferous zwitter and tourmalinite with associated rare metal mineralization.
Keywords: rare metals; Li-F granites; biotite; greisen; zwitter; tourmalinite; chloritite; Verkhneurmiysky ore cluster; Far East of Russia